2011
DOI: 10.1002/jid.1794
|View full text |Cite
|
Sign up to set email alerts
|

Should I stay or should I go? Return migration in times of crises

Abstract: Abstract:The current economic downturn has a significant impact on migrants' lives, including their considerations of return. Massive returns have potentially disastrous consequences for migrants' countries of origin, especially those countries that have become dependent on remittances. Yet, return is the least understood part of the migration process. Based on comparative observations of the same group of migrants following the Argentinean crisis in 2001 and the current economic downturn in Spain, this paper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 11 publications
0
56
0
11
Order By: Relevance
“…Homeownership and bank account-considered as forms of saving-are positively associated with settlement intention, as stated by numerous studies (Da Vanzo 1983;Massey 2002, 2003;Bastia 2011;Delpierre and Verheyden 2014). The relationship between professional status and desired length of stay reflects gender roles.…”
Section: Length Of Staymentioning
confidence: 92%
See 1 more Smart Citation
“…Homeownership and bank account-considered as forms of saving-are positively associated with settlement intention, as stated by numerous studies (Da Vanzo 1983;Massey 2002, 2003;Bastia 2011;Delpierre and Verheyden 2014). The relationship between professional status and desired length of stay reflects gender roles.…”
Section: Length Of Staymentioning
confidence: 92%
“…Specifically, homeownership is commonly considered as strongly connected to the decision or intention to stay (Da Vanzo 1983;Massey 2002, 2003;Bastia 2011;Delpierre and Verheyden 2014). Similarly, each form of savings in the host country is associated with permanent settlement or longer stay (Delpierre and Verheyden 2014).…”
Section: Deciding To Staymentioning
confidence: 99%
“…Internationally, migration has been profoundly affected by the crisis, with the growth of immigration in Western Europe and the United States coming to a standstill (Papademetriou, Sumption, & Terrazas, 2011;'The people crunch' , 2009). Bastia (2011) found that family and health reasons were dominant in the return migration decision of Bolivian and Argentinean migrants to Spain even during the present economic crisis, and that those who stayed were willing to make sacrifices on their pay and employment conditions to remain. Historically, Green and Winters (2010) noted that though economic crises such as the Irish Potato Famine had a significant impact on migration, the general pattern over time is only a weak relationship between emigration and economic growth.…”
Section: International Migrationmentioning
confidence: 99%
“…7 Núm 1 (2016) 75-88 empiezan a discutir la categoría de circularidad de las migraciones para aprehender estas dinámicas (Baldassar y Merla 2014). En este campo, pocos trabajos han adoptado una perspectiva de género para entender este nuevo momento de las migraciones andinas y lo han hecho sobre todo respecto a la migración boliviana (Bastia 2011, Yépez y Marzadro 2014.…”
Section: Introductionunclassified